The Fundamental Concept of Educational Innovation: Through Innovation in Thinking, Environment, Culture, and Behaviour - Yuni Wulandari; Tasya, Tasya (INFOKUM, 2025)
The main objective of national education in general is to improve the quality of human resources (HR) through various educational management processes and educational innovation. This study aims to provide an understanding of the basic concept of innovation in educational management, which includes innovation in thinking, environment, culture, and human behavior. This research is included in the category of library research, which is conducted by reading, reviewing, and examining books and written sources related to issues of educational innovation and educational management. The results of this study reveal that educational management innovation can be achieved through thinking that considers environmental and cultural situations, and focuses on the formation of student behavior and the development of human resources in the world of education to become individuals with morals and professionals. The innovations carried out include the implementation of school-based management, curriculum changes, online-based data collection, and innovations in human resource management. In implementing these innovations, it is necessary to provide quality and innovative human resources, adequate support, and the creation of a conducive climate to support the success of the educational process.